Evaluation of the Effectiveness of Riamilovir in Prevention of COVID-19: Mathematical Simulation Results - A. S. Sigidaev; P. B. Zotov; V. A. Duldin; I. I. Iva; K. V. Kozlov; O. V. Maltsev; V. V. Ivanova; K. Bryanskaya-Kasyanenko (Антибиотики и Химиотерапия)
Aim. Evaluation of the effectiveness of the preventive use of the directacting antiviral drug riamilovir in reducing the incidence of COVID-19, as well as its impact on the dynamics of infection spread using mathematical simulation on the example of the Kurgan region population to optimize preventive strategies for epidemiologically significant diseases.   Material and methods. To simulate the spread of COVID-19 in the Kurgan region, the extended SEIR model was used, taking into account the effect of riamilovir on the likelihood of contracting a new coronavirus infection. The numerical solution of the system of differential equations was carried out using the 4th order Runge-Kutta method. The input parameters of the modelwere based on demographic data from the region and the results of a clinical study of riamilovir preventive efficacy against COVID-19 and acute respiratory viral infections. The scenarios under consideration involve 30 % and 50 % of the population taking the drug, which reduced the likelihood of infection by 25.7 % and 40 %, respectively.   Results. Based on mathematical simulation, it has been established that the preventive use of riamilovir by 30% or 50% of the population shifts the peak of the epidemic to a later date, and the maximum number of active cases is significantly reduced compared to the scenario without the drug. The total number of cases is decreasing, which reduces the burden on the healthcare system and improves control over the spread of infection.   Conclusion. Mathematical simulation has shown that the scenario of preventive use of riamilovir on the example of the Kurgan region can significantly reduce the incidence of infections with epidemic potential, reduce the burden on the healthcare system, and slow down the peak of the epidemic.